EDUCATIONAL ACCOUNTABILITY OF THE AS SHIDDIIQI INTEGRATED ISLAMIC ELEMENTARY SCHOOL IN IMPLEMENTING TWELVE YEARS OF COMPULSORY EDUCATION POLICY IN JAMBI CITY - Musli - (INNOVATIO: Journal for Religious Innovations Studies, 2023)
Basic education is the human right of every Indonesian human being as mandated by the 1945 Constitution, the research method is carried out by qualitative research, the educational accountability of the As Shidiiqi Integrated Islamic elementary school participates in the alleviation of the twelve year compulsory education policy, The educational accountability of the As Shidiiqi Islamic private elementary school in the implementation of the twelve-year compulsory education policy in the city of Jambi is carried out, among others, by completing and improving facilities and infrastructure, teaching and learning processes and evaluations that follow standards set by the government and JSIT, attitude and role of stakeholders in implementing accountability for completing twelve years of compulsory education, and several policies carried out by the school that support the implementation of accountability for completing the twelve year of compulsory education and accountability. Pendidikan dasar merupakan hak asasi setiap manusia Indonesia sebagaimana yang diamanatkan oleh UUD 1945, metode penelitian yang dilakukan dengan penelitian kualitatif, akuntabilitas pendidikan sekolah dasar Islam Terpadu As Shidiiqi turut serta dalam pengentasan kebijakan wajib belajar dua belas tahun, Akuntabilitas pendidikan sekolah dasar swasta Islam Terpadu As Shidiiqi dalam pelaksanaan kebijakan wajib belajar dua belas tahun di kota Jambi dilakukan diantaranya dengan pelengkapan dan peningkatan sarana dan prasarana, proses belajar mangajar dan evaluasi yang mengikuti standar yang telah ditetapkan oleh pemerintah dan JSIT, sikap dan peran serta stakeholder dalam pelaksanaan akuntabilitas manuntaskan wajib belajar dua belas tahun, dan beberapa kebijakan yang dilakukan pihak sekolah yang menunjang pelaksanaan akuntabilitas manuntaskan wajib belajar dua belas tahun dan akuntabilitas